Influence of planting geometries on tuber yield and profitability of seed potatoes (Solanum tuberosum) in north-western plains of India - KUMAR, RAJ; KUMAR, PRINCE; SHAH, MOHD ABAS; SINGH, RAJESH KUMAR; SHARMA, ASHWANI KUMAR; SHARMA, JAGDEV (The Indian Journal of Agricultural Sciences, 2023)
The present field experiment was conducted during winter (rabi) seasons of 2018–19 and 2019–20 at ICAR-Central Potato Research Institute, Regional Station Jalandhar, Punjab to find out the suitable planting geometry and dehaulming date for enhancing the seed potato (Solanum tuberosum L.) yield and profitability under north-western plains of India. According to the study planting geometry and dehaulming date strongly influenced the seed size tuber yield and quality. Among the different planting geometries, paired row bed planting significantly increased the yield and number of seed size tubers when dehaulming was done after 80–90 days. Maximum gross income, net returns and benefit:cost ratio was also observed under paired row bed planting over the conventional planting geometry. Paired row bed planting increased the tuber yield by 21.7% and benefit:cost ratio by 18.6% over the control. Hence, it is concluded from the experiment that paired row bed planting is found suitable for maximizing the seed size tuber numbers, yield as well as getting the maximum economic returns.